A national study of the mental health status of Asian international students in the United States. Issue 2 (28th March 2022) - Xiong, Yiying; Pillay, Yegan
Abstract: This study compared the mental health status of Asian international students (AIS) in the United States with American students and other international students by analyzing 4 years of data (2011–2014) from the American College Health Association‐National College Health Assessment. No significant differences were found in the ***AIS' psychological distress, but their self‐reported self‐harm ideation and behavior were higher than the other two groups. Predictors of psychological distress were analyzed and implications for stakeholders are offered. Resumen: Este estudio comparó el estado de salud mental de estudiantes internacionales asiáticos (AIS, por sus siglas en inglés) en Estados Unidos con el de estudiantes americanos y de otros grupos internacionales mediante el análisis de cuatro años de datos (2011‐2014) obtenidos de las Evaluaciones Nacionales de Salud Universitaria de la Asociación Americana de Salud Universitaria (ACHA‐NCHA, por sus siglas en inglés). No se hallaron diferencias significativas en el sufrimiento psicológico de los AIS, pero sus niveles autorreportados de ideación y comportamiento de autolesiones fueron más elevados que en los otros dos grupos. Se analizaron los predictores de sufrimiento psicológico y se ofrecen implicaciones para las partes interesadas.